Multiview Implementation in Open CV-based Crescent Observation Application - Damanhuri, Adi; Samun, Samun; Solikin, Agus (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2023)
Determining the beginning of the Hijri month is very important for Muslims, especially in Indonesia. One way to determine the beginning of the month is by observing the new moon or moon sighting. In the process of hilal (crescent) sighting, there are theoretically obstacles related to the validity of the sighting results. By implementing an observation system that has the function of displaying and storing observations through a developed application, it is hoped that it can help to increase the validity of the new moon observation. This study answers two problem formulations, specifically: (1) Can an OpenCV-based new moon observation application be built? (2) Can the multiview function be implemented with OpenCV? By using the Phyton programming language, the OpenCV library, and other additional libraries, an OpenCV-based new moon observation application has been successfully created, and at the same time the Multiview function has been implemented. The used application works well, especially the multiview function and the function to save the observations in the specified image format.